The concept of the entrepreneurial agreement under the law of the Republic of Kazakhstan - Kusainov, D.; Kusainova, A.K. (Journal of actual problems of jurisprudence, 2018)
The article deals with the problem of the definition of an entrepreneurial agreement , his relationship with the contract. It defines specific subject structure of the entrepreneurial agreement – one of the sides of it must be the subject of law, endowed with the status of entrepreneur and engaged in entrepreneurial activity. Key words: entrepreneurial agreement, a contract, entrepreneurship, entrepreneurial revolution, relations with the participation of anentrepreneur.